Functional and Bioactive Properties of Food - Diego A. Moreno (Ed.)
Diet and nutrition are key tools in promoting health and reducing the comorbidities of chronic diseases. There are thousands of biomolecules in fruits, vegetables, wild and medicinal plants, other land and marine organisms, which can exert functional and health-promoting effects through bioactivity beyond nutrition. From the enormous amount of knowledge generated from different natural bioactive ingredients present in foods, we are aiming to bring together experts working in different fields of food, nutrition, and health, in order to work on this Special Issue, with a comprehensive collection of papers to gain insight into the most promising bioactive compounds in different foods, to improve the preservation of bioactivity during the food processing chain, and to provide scientific evidence of the efficacy of key bioactives in foods in preventing disease and improving health and wellbeing.